PrEP4Love: The Role of Messaging and Prevention Advocacy in PrEP Attitudes, Perceptions, and Uptake Among YMSM and Transgender Women. (15th April 2020) - Phillips, Gregory; Raman, Anand B.; Felt, Dylan; McCuskey, David J.; Hayford, Christina S.; Pickett, Jim; Lindeman, Peter T.; Mustanski, Brian
Abstract : Background: Despite high efficacy, use of pre-exposure prophylaxis (PrEP) remains low among young men who have sex with men (MSM) and transgender women (TW), primarily because of barriers such as stigma and resource awareness. We evaluated a social marketing campaign known as PrEP4Love that works to eliminate PrEP stigma; and awareness gaps through targeted advertising. Setting: Chicago, Illinois. Methods: Participants were enrolled within a cohort study of young MSM and TW (RADAR). Data were collected between June 2017 and April 2018 from HIV-negative individuals attending a follow-up visit. Surveys assessed demographics, PrEP attitudes and perceptions, and PrEP4Love campaign awareness. Associations between PrEP4Love awareness and PrEP perceptions, uptake, and behaviors were assessed using multiple logistic regression controlling for age, race/ethnicity, gender, sexual identity, and ever having used PrEP. Results: Of 700 participants, the majority (75.9%) indicated seeing PrEP4Love ads in Chicago. Those who had seen ads were more likely to be out to their providers (odds ratio = 1.95; 95% confidence interval: 1.17 to 3.23) than those who had not, and those who had conversations were significantly more likely to have initiated the conversation themselves. Individuals who had seen ads were more likely to have taken PrEP in the last 6 months (odds ratio = 1.87; 95% confidence interval: 1.15 to 3.16) and more likely to believe their friends and the general public approved of and used PrEP. Conclusion: Social marketing campaigns are promising interventions that have the potential to alleviate barriers to HIV prevention, particularly among MSM and TW. Future research should evaluate the impact of these initiatives at multiple time points.